Linear oblique craniectomy: A novel method of minimally invasive subdural grid insertion. Issue 2 (23rd November 2020) - Howard, Calvin W; Aboelnazar, Nader S; Salem, Noor; Syed, Naweed; Willetts, Lian
Background: Many countries rely upon subdural grid electroencephalography in the planning of epilepsy surgeries. However, craniotomy for subdural grid implantation is known to result in a variety of complications and requires diligence from the surgical team. We describe a minimally invasive method of subdural grid insertion, termed the linear oblique craniectomy, designed to mitigate complications and increase ease of subdural grid insertion. Objective: To demonstrate feasibility of minimally invasive subdural grid insertion utilizing skull anatomy. Methods: Three fresh frozen and embalmed human cadavers underwent surface landmarking and craniectomy to introduce a 4 × 5 cm 2 subdural grid over the Sylvian fissure. Anteroposterior lens-shaped craniectomy measured 5 cm in length with 1 cm maximal width. The dura mater was longitudinally incised, and subdural grids were introduced over the Sylvian fissure. Results: The total area of the craniectomy created by the linear oblique approach consists of only approximately 20% of the total area removed by the traditional approach to access the Sylvian fissure for mesial temporal epilepsy monitoring/preoperative planning. The locations of the grids were evaluated by MRI and computed tomography scans postoperatively to ensure accurate alignment with the Sylvian fissure. Conclusion: In this cadaveric study, we demonstrate the linear oblique craniectomy procedure that provides an alternative approach to subdural grid implantation with significantly decreased invasiveness. This surgical approach has the potential of reducing complication rates of subdural grid insertion for surface monitoring of the brain activity and/or neuromachine interface analysis and is associated with significant reduction of surgical time.